Identification of the prfC gene, which encodes peptide-chain-release factor 3 of Escherichia coli. - Mikuni, O (1994)
The termination of protein synthesis in bacteria requires two codon-specific polypeptide release factors, RF-1 and RF-2. A third factor, RF-3, which stimulates the RF-1 and RF-2 activities, was originally identified in Escherichia coli, but it has received little attention since the 1970s. To search for the gene encoding RF-3, we selected nonsense-suppressor mutations by random insertion mutagenesis on the assumption that a loss of function of RF-3 would lead to misreading of stop signals. One of these mutations, named tos-1 (for transposon-induced opal suppressor), mapped to the 99.2 min region on the E. coli chromosome and suppressed all three stop codons. Complementation studies and analyses of the DNA and protein sequences revealed that the tos gene encodes a 59,442-Da protein, with sequence homology to elongation factor EF-G, including G-domain motifs, and that the tos-1 insertion eliminated the C-terminal one-fifth of the protein. Extracts containing the overproduced Tos protein markedly increased the formation of ribosomal termination complexes and stimulated the RF-1 or RF-2 activity in the codon-dependent in vitro termination assay. The stimulation was significantly reduced by GTP, GDP, and the beta,gamma-methylene analog of GTP, but not by GMP. These results fit perfectly with those described in the original publications on RF-3, and the tos gene has therefore been designated prfC. A completely null prfC mutation made by reverse genetics affected the cell growth under the limited set of physiological and strain conditions.